2022
DOI: 10.1136/bmjopen-2021-052595
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of help-seeking by parents for the socioemotional development of their 3-year-old children: a longitudinal study

Abstract: ObjectivesTimely parental help-seeking regarding their child’s socioemotional development is associated with a lower rate and lower severity of psychosocial problems in later life. This study aimed to examine the correlates of parental help-seeking for the socio-emotional development of 3-year-old children.DesignRetrospective cohort study.SettingCommunity-based survey in Rotterdam.ParticipantsOf 2305 parents and their 2-year-old children at baseline, 1507 who completed follow-up questionnaires were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The study results found that 22.6% parents reported help-seeking behavior, among them 6.8% addressed from formal help sources and 17.5% from informal sources. Luo (2022) Present study findings also supported by another study on Parent identification and help-seeking behavior around child mental health difficulties conducted by Game S (2019). The study result revealed that 78% of parents correctly identified their child had mental health problem, consistently around 50% of these parents asked for help.…”
Section: Findings On Health Seeking Behavior Of Mothers Of School Chi...supporting
confidence: 90%
“…The study results found that 22.6% parents reported help-seeking behavior, among them 6.8% addressed from formal help sources and 17.5% from informal sources. Luo (2022) Present study findings also supported by another study on Parent identification and help-seeking behavior around child mental health difficulties conducted by Game S (2019). The study result revealed that 78% of parents correctly identified their child had mental health problem, consistently around 50% of these parents asked for help.…”
Section: Findings On Health Seeking Behavior Of Mothers Of School Chi...supporting
confidence: 90%
“…Another cohort (cohort 2) studied questionnaire pressure when identifying psychosocial problems. More details can be found elsewhere [ 25 ]. The data from these two observational cohorts were combined to enlarge the sample size in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Parental education level was the highest level of education finalized by the respondent and their partner and categorized as high, middle, or low following the Classification of Statistics Netherlands [ 26 ]. Unemployment and financial problems in the family were derived from 12 stressful stress events based on Tiet et al’s [ 25 ] Adverse Life Events Scale. Participants were asked whether unemployment happened in the family in the past 2 years when child age 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…At two follow-ups, data were available for 1540 and 1257 children at the ages of 36 months and 45 months, respectively. More details can be found elsewhere [ 17 ]. Regarding the information on children, we excluded cases with missing data on stressful life events ( n = 86), with only one measurement of psychosocial problems, general health, or both ( n = 639), and with missing data on potential confounders ( n = 149).…”
Section: Methodsmentioning
confidence: 99%